Characterization of uranium redox state in organic-rich Eocene sediments. (March 2018) - Cumberland, Susan A.; Etschmann, Barbara; Brugger, Joël; Douglas, Grant; Evans, Katy; Fisher, Louise; Kappen, Peter; Moreau, John W.
Abstract: The presence of organic matter (OM) has a profound impact on uranium (U) redox cycling, either limiting or promoting the mobility of U via binding, reduction, or complexation. To understand the interactions between OM and U, we characterised U oxidation state and speciation in nine OM-rich sediment cores (18 samples), plus a lignite sample from the Mulga Rock polymetallic deposit in Western Australia. Uranium was unevenly dispersed within the analysed samples with 84% of the total U occurring in samples containing >21 wt % OM. Analyses of U speciation, including x-ray absorption spectroscopy and bicarbonate extractions, revealed that U existed predominately (∼71%) as U(VI), despite the low pH (4.5) and nominally reducing conditions within the sediments. Furthermore, low extractability by water, but high extractability by a bi-carbonate solution, indicated a strong association of U with particulate OM. The unexpectedly high proportion of U(VI) relative to U(IV) within the OM-rich sediments implies that OM itself does not readily reduce U, and the reduction of U is not a requirement for immobilizing uranium in OM-rich deposits. The fact that OM can play a significant role in limiting the mobility and reduction of U(VI) in sediments is important for both U-mining and remediation. Highlights: 84% of U in Mulga Rock OM-bearing sediments occurred within the OM-richest samples (>21% TOC; 9 of 18 samples). 71% of U was present in the U(VI) oxidation state. Higher proportions of U occur as U(VI) in mature OM-rich sediments than previously thought. OM strongly complexes U(VI), limiting its mobility and reactivity. U reduction processes are not ubiquitous within OM-rich sediments.